2019
DOI: 10.1590/0034-7167-2018-0446
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ competencies in health promotion for homebound older people

Abstract: Objective: to identify competencies related to health promotion targeting homebound older people, as they appear in the literature. Method: systematic review using the LILACS, Scopus, CINAHL, PubMed and Cochrane Library databases. The search was performed in November 2017. Selected articles were analyzed according to nine competency domains: enable change; advocate for health; mediate through partnership; communication; leadership; assessment; planning; implementation, and evaluation and research. Results: n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…In the planning of HE interventions, we clarified a planning with the evaluation of health needs, and, consequently, lines of action capable of acting on health determinants, adapted to the complexity of both the children and parents, and each child’s/young person’s life cycle. In parallel, studies reported that, in order to intervene, planning based on evaluation is necessary, and thus effective implementation leads to well-planned activities [ 24 ], allowing health professionals to better take advantage of opportunities; better define objectives; organize activities and interventions; and monitor, inspect, and evaluate the results [ 25 ]. The use of improvisation demonstrated the capacity for creativity and taking advantage of all opportunities in HE practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the planning of HE interventions, we clarified a planning with the evaluation of health needs, and, consequently, lines of action capable of acting on health determinants, adapted to the complexity of both the children and parents, and each child’s/young person’s life cycle. In parallel, studies reported that, in order to intervene, planning based on evaluation is necessary, and thus effective implementation leads to well-planned activities [ 24 ], allowing health professionals to better take advantage of opportunities; better define objectives; organize activities and interventions; and monitor, inspect, and evaluate the results [ 25 ]. The use of improvisation demonstrated the capacity for creativity and taking advantage of all opportunities in HE practice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nursing leadership can produce changes in care systems, establishing partnerships and adequate communication between professionals and the community. Still, it is highlighted that nurses can lead teams as well as support other professionals through supervision and dialogue (17)(18) .…”
Section: Catalyzing Change […] Regarding the Prevention Of Cervical And Breast Cancer From Time To Time I'll Do An Educational Practice [mentioning
confidence: 99%
“…2.436/17, which approves the National Policy on Primary Care, the duties of nurses working in Primary Care are described: carrying out nursing consultations, requesting additional tests, and prescribing medications, following the legal provisions of the profession in compliance with protocols or other technical regulations established by the Ministry of Health. Such elements demonstrate the autonomy that these professionals can and should exercise in the health service (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) .…”
Section: Catalyzing Change […] Regarding the Prevention Of Cervical And Breast Cancer From Time To Time I'll Do An Educational Practice [mentioning
confidence: 99%
“…Em paralelo, o grau de vulnerabilidade do idoso é comumente representado pelo termo "fragilidade" e, considerando o adoecimento desse grupo, aliado ao processo biológico de envelhecimento, há uma potencialização das condições de fragilidade, incapacidades e perda de autonomia, deixando este grupo vulnerável e, na maioria das vezes, cronicamente dependente do cuidado de outros (Leandro et al, 2019).…”
Section: Introductionunclassified
“…O cuidado da enfermagem deve ser sistematizado, para que se atinja a resolubilidade das necessidades de saúde da população, qualificação e segurança ao ser ofertado (Adamy, Zocche, & Almeida, 2020). A avaliação como parte do processo de cuidar é relevante na definição do plano de cuidados, e, em se tratando de pessoas idosas no domicílio, este se se estende também à família (Barbosa, Nascimento, Carvalho, Aoyama, & Lima, 2019;Leandro et al, 2019).…”
Section: Introductionunclassified